Mobility Oriented Link Extent and Quality Aware Routing (MLEQR) Based On SS-PSO in MANETs - P. Shailaja, C.V. Guru Rao (International Journal of Advanced Science and Technology, 2020)
Link Quality and Link Stability are the two important factors which have a serious effect on the Quality of Service due to the dynamic moving nature of mobile nodes in MANETs. In this paper, we focused to analyze the effect of mobility on the Link Lifetime and proposed a new approach called as Mobility Oriented Link Extent and Quality Aware Routing (MLEQR) for routing in MANETs. According to MLEQR, each node measures the Link Extent Time and Link Quality of neighbor nodes before selecting them as a next-hop forwarding nodes. Here the Link Extent Time and Link Quality are modeled through Location and Delay constraints respectively. Under delay constraint, a weight factors is computed based on the Neighbor Node Intimacy and Packet Delivery Ratio. Finally a composite route metric is modeled by integrating the Link Extent Time and Weight factor. And a weighted Particle Swarm Optimization is employed for optimization. Simulation experiments are conducted over the proposed routing model and the performance is measured through Packet Delivery ratio, Throughput and End-to-End Delay. Further the simulation results of proposed approach are compared with several conventional approaches had proven the outstanding performance.